Pregnancy in a patient with paroxysmal nocturnal hemoglobinuria - Singh, Anju; Sikka, Pooja; Suri, Vanita; Agrawal, Neelam; Chopra, Seema; Kumar, Bhupesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
The occurrence of Paroxysmal Nocturnal Hemoglobinuria (PNH) during pregnancy is very rare. It can cause significant fetomaternal morbidity and mortality due to associated complement mediated hemolysis and/or thrombosis. We report a case of PNH in a pregnant lady who presented to our antenatal clinic at 10th weeks of gestation. Her pregnancy was managed with multiple blood transfusions and steroid administration. During 3rd weeks postpartum period she developed sepsis with acute renal failure and posterior reversible encephalopathy syndrome requiring prolonged hospitalization. She was subsequently discharged from hospital in satisfactory condition.